Clay Mask Formulation with Moringa oleifera Leaf Extract and Antibacterial Activity Against Staphylococcus aureus - Dewi, Nila Audri Risdiana; Rahmawati, Ismi; Purnamasari, Nur Aini Dewi (Indonesian Journal of Pharmaceutical Education, 2025)
Moringa leaves contain tannins, flavonoids, phenols, alkaloids and steroids as antibacterials. One of the causes of acne is Staphylococcus aureus infection. Cosmetic clay mask that can be used for acne skin care. Variations in kaolin concentration can affect the drying time of clay mask preparations. This research aims to determine the clay mask formula for Moringa leaf extract with a variety of kaolin which has physical quality, good stability and antibacterial activity against S. aureus. This research uses 10% Moringa leaf active ingredient which is extracted using the maceration method with 70% ethanol. The clay mask formula consists of kaolin, bentonite, glycerin, DMDM hydantoin, xanthan gum, rose oil and distilled water. The clay mask formula made has varying kaolin concentrations of 30% (F1), 35% (F2) and 40% (F3). The results of formulations F1, F2, and F3 were tested for physical quality and stability and tested for antibacterial activity against S. aureus ATCC 25923. The statistical test for the activity of clay masks F1, F2, and F3 was not significantly different (Sig0.05), but F2 had the highest inhibitory power.  The statistical results of the stability of F1, F2, and F3 are not significantly different (Sig0.05). The results of research on Moringa leaf extract clay masks with variations in kaolin concentration. F1 did not meet the adhesion and viscosity test requirements, while F2 and F3 have physical quality and stability tests that meet the requirements. Moringa leaf extract clay mask has strong antibacterial activity against S. aureus in all three formulas. F1, F2 and F3 with a diameter resistance of 17.44 respectively; 18.56 and 17.67 mm. F2 is the best Moringa leaf extract clay mask formula based on physical quality, stability and antibacterial activity against S. aureus.